Design on Master Controller Performance Detecting Device for Metro Vehicle - 杜连超 (机车电传动)
The working principle of master controller was analyzed, and necessity of master controller performance testing was pointed out. According to the logical relationship between the operations of master controller, the detecting device’s hardware and software were designed, and test methods were described in detail for making comments on master controller performance.